2020
DOI: 10.1101/2020.09.10.281949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of Zika virus xrRNA1-dependent sfRNA1 production results in tissue-specific attenuated viral replication

Abstract: Zika virus (ZIKV), like other flaviviruses, produces several species of sub-genomic RNAs (sfRNAs) during infection, corresponding to noncoding RNA fragments of different lengths derived from the viral 3’ untranslated region (UTR). Over the course of infection, these sfRNAs accumulate in the cell as a result of incomplete viral genome degradation of the 3’UTR by host 5’ to 3’ exoribonuclease (Xrn1). The halting of Xrn1 in the 3’UTR is due to two RNA pseudoknot structures in the 3’UTR termed exoribonuclease-resi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, as this deletion causes major structural disruption in viral 3′UTR, which is also required for viral replication ( 40 ), this model does not allow separation of the effects caused by sfRNA deficiency from the effect of compromised genome integrity. Another study used partially sfRNA-deficient ZIKV (still producing sfRNA2, equivalent to our xrRNA1′ mutant) and found that the mutation did not affect viral replication in cell lines while causing reduced maternal blood viremia and placental viral loads in a mouse pregnancy model ( 41 ). However, this study could not assess the effect of sfRNA on transplacental virus dissemination and fetal brain infection, as even WT ZIKV in these experiments was not detected in fetal heads ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as this deletion causes major structural disruption in viral 3′UTR, which is also required for viral replication ( 40 ), this model does not allow separation of the effects caused by sfRNA deficiency from the effect of compromised genome integrity. Another study used partially sfRNA-deficient ZIKV (still producing sfRNA2, equivalent to our xrRNA1′ mutant) and found that the mutation did not affect viral replication in cell lines while causing reduced maternal blood viremia and placental viral loads in a mouse pregnancy model ( 41 ). However, this study could not assess the effect of sfRNA on transplacental virus dissemination and fetal brain infection, as even WT ZIKV in these experiments was not detected in fetal heads ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study used partially sfRNA-deficient ZIKV (still producing sfRNA2, equivalent to our xrRNA1′ mutant) and found that the mutation did not affect viral replication in cell lines while causing reduced maternal blood viremia and placental viral loads in a mouse pregnancy model ( 41 ). However, this study could not assess the effect of sfRNA on transplacental virus dissemination and fetal brain infection, as even WT ZIKV in these experiments was not detected in fetal heads ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that deleterious mutations, as well as RNA structure-altering mutations in the flavivirus 3'UTR led to reduced viral burden and pathogenesis in mouse models 14,21,26,[28][29][30][31] . To investigate potential alterations in the pathogenesis of our ZIKV DB-1 mutant clones, we used an AG129 mouse model for ZIKV infection.…”
Section: Analysis Of Zikv-tlpk and Zikv-p25' In Murine Modelmentioning
confidence: 99%
“…In some TBE viruses, there are seven stem-loops: SL1-SL7 (Sakai et al, 2015;Ochsenreiter et al, 2019). These SL structures are conserved among flaviviruses and are responsible for the inhibition of the activity of Xrn-1 nuclease, an important process for the generation of sfRNAs, which participate in the antiviral evasion mechanisms in both mammals and mosquitoes (Funk et al, 2010;Villordo et al, 2015;Göertz et al, 2016;Chen et al, 2018;Bellone et al, 2020), including viral adaptation, fitness, virulence, and tissue tropism (Funk et al, 2010;Liu et al, 2018;Finol and Ooi, 2019;Sparks et al, 2020). In WNV, the SL-III has an inhibitory effect on translation since its deletion increase viral translation efficiency (Berzal-Herranz et al, 2022).…”
Section: Flavivirus 3' Utrmentioning
confidence: 99%
“…The nomenclature referred by Liu et al, 2018 for the stem loops present in the variable region are in parenthesis. The variable regions of West Nile (WNV- Tilgner et al, 2005;Funk et al, 2010;Clarke et al, 2015, andGöertz et al, 2016), Japanese encephalitis (JEV- Chen et al, 2018 andXing et al, 2021), Tick borne encephalitis (TBEV- Muto et al, 2018 andSakai et al, 2015) and Zika viruses (ZIKV- Schneider andSparks et al, 2020) are shown. Additionally, the first dumbbell structure of ZIKV (Schneider and Wolfinger, 2019) is also included.…”
Section: Flavivirus 3' Utrmentioning
confidence: 99%